Relationship between asprosin and certain biochemical parameters in obese patients - N. S. Humadi; N. A. Saleh (Regulatory Mechanisms in Biosystems, 2025)
Obesity is a widespread health issue among children and adolescents, driven by genetic and environmental factors. It results from low energy expenditure and excessive caloric intake, leading to complications like hypertension, metabolic disorders, card i ovascular disease, diabetes, and arthritis. The current study aimed to estimate the levels of asprosin, leptin, adiponectin, and zinc in obese individuals and to analyze their correlation with obesity-related metabolic disorders. The study collected 60 blood sa m ples from obese individuals (30 males, 30 females) and 60 from healthy controls in Baghdad, Iraq. Asprosin, leptin, and adip o nectin levels were measured using ELISA, involving antibody reactions and spectrophotometric detection at 450 nm. Zinc co n centration was determined through its reaction with 5-Br-PADAP, forming a color complex measured at 560 nm. The findings revealed an increase in asprosin levels in obese individuals, supporting its role as a potential biomarker for obesity and metabolic disorders. Additionally, leptin levels were elevated in obese subjects, while adiponectin and zinc levels were significantly lower in comparison to healthy controls. This study highlights the potential role of asprosin as a biomarker and therapeutic target for obesity. The observed alterations in leptin, adiponectin, and zinc levels further emphasize the metabolic dysregulation associated with obesity.